2020
DOI: 10.1186/s41610-020-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microplastics and salinity on food waste processing by black soldier fly (Hermetia illucens) larvae

Abstract: Background: The black soldier fly (Hermetia illucens) is gaining attention as an efficient decomposer of food waste. However, recalcitrant compounds such as plastics mixed into food waste may have negative effects on its growth and survival. Moreover, its efficiency of food waste degradation may also be affected by plastics. In addition, salt (NaCl) can also be present in high concentrations, which also reduces the efficiency of H. illucens-mediated food waste treatment. In this study, we assessed the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 37 publications
8
29
0
Order By: Relevance
“…In this preliminary study, a single MP concentration was tested against the control to determine whether MPs could potentially influence the survival, growth, development or fatty acid composition of BSFL. Both the survival and growth of BSFL were unaffected by MP exposure, which is consistent with Cho et al (2020); however, there were two contrasting findings between our study and Cho et al (2020). First, PP‐MPs had no effect on substrate reduction in this study, and second, the percentage of larvae reaching the pre‐pupae stage was significantly reduced after PP‐MP exposure in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this preliminary study, a single MP concentration was tested against the control to determine whether MPs could potentially influence the survival, growth, development or fatty acid composition of BSFL. Both the survival and growth of BSFL were unaffected by MP exposure, which is consistent with Cho et al (2020); however, there were two contrasting findings between our study and Cho et al (2020). First, PP‐MPs had no effect on substrate reduction in this study, and second, the percentage of larvae reaching the pre‐pupae stage was significantly reduced after PP‐MP exposure in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, one gram of the MP treatment would contain 26,972 particles (or 26,972,507 particles/kg) based on dividing 1,621,856 particles by 60.13 g (substrate of 0.60 g plus 0.13 of the MPs). The tested MP concentration of 0.022 g/kg in this study is a fraction of those used in other studies on insects, such as 1.25 to 20 g/kg (Silva et al, 2019) and 0.2 g/kg (Cho et al, 2020). Nevertheless, the levels used in this study are substantially higher than those found in nature ranging from 112 to 234 particles/kg in Italian lakes (Fischer et al, 2016) to 3,153 particles/ kg in Poyang Lake (Liu et al, 2019) and 91,000 particles/kg in various unmanaged landfills (He et al, 2019;Hou et al, 2021;Su et al, 2019).…”
Section: Experimental Design Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated salt (NaCl) content in meals is often discussed because of its adverse effect on human health (e.g., high blood pressure) and can account for up to 1.2% in hot meals and sandwiches handed out in canteens ( Rasmussen et al, 2010 ). Cho et al (2020) concluded that BSFL are suitable to treat food waste with even higher salt concentrations, since a significant inhibition of biomass gain and pupation was only observed at concentrations >3%.…”
Section: Introductionmentioning
confidence: 99%